Systematic Review and Meta-Analysis of the Effects of Soy on Glucose Metabolism in Patients with Type 2 Diabetes (The Review of Diabetic Studies, 2019)
OBJECTIVE: This study aimed to assess the effects of soy consumption on glucose metabolism in patients with type 2 diabetes. METHODS: A systematic review was performed in accordance with the Preferred Reporting Items for Systematic Review (PRISMA) principles. Literature published between 1990 and 2019 was searched. Primary outcomes were the effect of soy on fasting plasma glucose (FPG), insulin, and HbA1c. The data were pooled using random effects models. Heterogeneity was assessed using Cochran’s Q and I 2 statistics. Also, the Cochrane Collaboration’s tool for assessing risk of bias was used, and sensitivity analysis and meta-regression were conducted. Publication bias was evaluated using Egger and Begg tests. RESULTS: Sixteen randomized clinical trials (RCTs) with a total of 471 participants were regarded as eligible and included in the study. Soy consumption had no significant effects on FPG, insulin, and HbA1c. After the “trim-and-fill” method was applied, soy revealed a significant effect size on FPG (adjusted Cohen’s d: -0.18; p = 0.03). Also, subgroup analyses using studies with parallel design showed a significant improvement (moderate effect size) in FPG and insulin. Sensitivity analysis indicated the robustness of our findings. Among secondary outcomes, the results showed a significant effect of soy on HOMA-IR and total cholesterol levels. CONCLUSIONS: Although this systematic review and meta-analysis indicated no beneficial effects of soy consumption on FPG, insulin, and HbA1c in patients with type 2 diabetes, pooling of parallel studies showed different results from crossover studies. The quality of evidence revealed low levels of confidence for primary outcomes. Therefore, further research is recommended.